Assessment of quality management practices’ maturity in palm oil organization / Nor Azmi Noor Saaid - Noor Saaid, Nor Azmi (Faculty of Plantation and Agrotechnology, 2018)
Malaysia palm oil is the biggest profits producing contributor for our economy. The palm oil industry is one and only of the highly organized sectors in agriculture which effectively balance each other’s to become more diversified sector. The quality management system implemented has not been effective and should be immediately carried out a corrective action to address such deviations. Quality management practices are lack of checklist system that needs to monitor the management, performance and handling in oil palm industry per day. This research attempts to comprehend the usage of maturity model in evaluating quality management in the industry to develop a checklist maturity level of management practices in palm oil organization. All the data had been used in this study is taken from primary document Malaysian Palm Oil Board, thesis and journals. This paper also presents a Systematic Literature Review (SLR) on assessment of quality management maturity practices in palm oil organization. The final selection comprehends 40 articles using SLR is selected and comprehensively analyzed to develop maturity checklist to ensure maturity level in palm oil organization. As a result, the maturity assessment had been developed that can be useful to improve the quality management practices in palm oil organization for a long term.